Kinematic and kinetic parameters to identify water polo players` eggbeater kick techniques - Kawai, E.; Gonjo, T.; Takagi, H. (Sports Biomechanics, 2021)
This study aimed to clarify the kinematic and kinetic parameters that identify the technical differences in the eggbeater kick. Twelve water polo players performed the eggbeater kick, and its kinematics were recorded by a motion capture system. Pressure distributions around the feet were measured by sixteen pressure sensors attached to the dorsal and plantar surfaces of the feet, from which the resultant fluid force acting on the feet and the vertical component of the force (i.e., propulsive force) were estimated. Repeated-measures analysis of variance (including post hoc test) results showed that the pressure difference, due to negative pressure on the dorsal side of the foot, around the first toe was significantly larger than the other foot segments (difference of up to 7 kN/m2, P <0.01). Moreover, cluster analysis (including Fisher information) results showed that the kinetic (fluid force and pressure) data had a major influence on clustering; the highest Fisher information was 10.42 for the mean propulsive force. Among the kinematic foot parameters, the influence of the foot angle data on clustering was large, suggesting its importance as a technical parameter of the eggbeater kick in relation to the kinetic data.